The occurrence of Rhynchophorus ferrugineus in Greece and Cyprus and the risk against the native greek palm tree Phoenix theophrasti - Kontodimas, D.C.; Milonas, P.G.; Vassiliou, V.; Thymakis, N.; Economou, D. (ENTOMOLOGIA HELLENICA, 2006)
The red palm weevil (RPW), Rhynchophorus ferrugineus (Coleopiera: Curculionidae), is the most important pest of palm trees in the world. In the last decade R. ferrugineus has invaded the Mediterranean basin where it causes severe damage in date palm cultivations as well as in ornamental palm trees. R. ferrugineus has been found for first time in Greece in Hersonissos (Heraklion district, Crete) infesting Phoenix canariensis, on November 11th, 2005 and for first time in Cyprus in Limassol district on August 20th, 2006, infesting also P. canariensis. Afterwards, R. ferrugineus has been found in Rhodos island, Greece, on 15/9/2006 and in Oropos and Ellinikon (Attiki district, Greece) on 5/12/2006 and 27/12/2006 respectively, infesting mainly P. canariensis. In Cyprus it has also been found in October 2006 in Larnaca, Famagusta and Paphos districts. In laboratory experimentation the susceptibility of the native Greek palm tree Phoenix theophrasti in R. ferrugineus was proved.